Desarrollar el nicho de mercado para la comercialización de sillas de plástico reciclado en la ciudad de Guaranda - Solis Cobos, Danny Stalin (2020)
The objective of this research is to develop the market niche for the commercialization of a recycled plastic chair in Guaranda City, currently the Plastic Industries in Ecuador are contributing to the economy and environmental conservation, in Guaranda solid waste fluctuates from two to five tons, with the application of digital surveys to the urban area to families, collecting real information and data executing the design of the chair with the application of the tool (function display QFD quality); in order to obtain information from the market segment on the requirements of our possible potential consumers, fulfilling expectations and providing an adequate service that is tailored to the needs, thus proceeding with the crushing of the plastic, washing, grinding, injection, entering molds and assembly, obtaining chairs 2m long by 1.1m high and 0.5m deep, obtaining an estimate of 12.235 chairs per year for a demand of 3,784 families. Keywords: Plastic, High and Low-Density Polyethylene, Market Niche, Quality Deployment, Sales Volume.